Disconnected during disruption: Energy insecurity of Indigenous Australian prepay customers during the COVID-19 pandemic. (May 2023) - Riley, Bradley; White, Lee V.; Wilson, Sally; Klerck, Michael; Napaltjari-Davis, Vanessa; Quilty, Simon; Longden, Thomas; Jupurrurla, Norman Frank; Harrington, Morgan
Abstract: Energy policy measures aimed at mitigating the impacts of energy insecurity during the first years of the COVID-19 pandemic, such as moratoriums on disconnection from electricity, were widespread. In Australia, early pandemic safeguards against electricity disconnection were successful in temporarily protecting most people. However, their application was uneven. For remote-living Indigenous community residents, who are required by policy or elect to use prepay metering and are known to experience frequent 'self-disconnection', energy insecurity continued as the impacts of the pandemic accrued. The risks associated with the regular de-energization of prepay households have long been overlooked by government reporting and this contributed to a lack of visibility of energy insecurity and available protections for this group during the pandemic response. In contrast to the rest of Australia, energy insecurity in the form of disconnections remained unrelentingly high or worsened for prepay households during this time. COVID-19 magnifies pre-existing health and socio-economic inequities. There is a need to pay closer attention to the rationales and impacts of energy policy exceptionalism if we are to mitigate the potential for compounding impacts of energy insecurity among specific groups, such as Indigenous Australian prepay customers, including during times of crisis.